Faktor Risiko Kejadian Stunted Pada Anak Usia 7-24 Bulan Di Desa Hargarejo, Kecamatan Kokap, Kabupaten Kulon Progo, Yogyakarta - Lestari, Restika Indah; , Dwi Sarbini, SST; , Luluk Ria Rakhma , S.Gz., M.Gizi (2016)
Government strives for their nutritional improvement of Indonesians through First Day of Life 1000 program (FDL), a nutrition program that is started since the fetus is in the womb until the child is 2 years old. One of the targets of this program is to decrease the prevalence of stunted to 32 % in under five children in 2015. Stunted and severe stunted are nutritional status based on indexs of the Length for Age (PB/U) or Height for Age (TB/U). Stunted occurs because of malnutrition in the long term that to impairment development of cognitive abilities, easily to get sicks and low competitiveness. To assess the correlations between histories of low birth weight, upper respiratory infections and diarrhea, intakes of protein and zinc and stunted in children aged 7-24 months in Hargorejo, Kokap, Kulon Progo, Yogyakarta. This was a cross sectional study. Number of subjects was 46 children aged 7-24 months. Histories of low birth weight, upper respiratory infections, and diarrhea, data were obtained from interviews, the intakes of protein and zinc data were obtained through the method of the Semi Qualitative-Food Frequency Questionnaire (SQ-FFQ) and length/height were obtained from measurements used length board or microtoise. Data were analyzed using Spearman Rank correlation and Pearson Product Moment test. Prevalence of stunted was 45,7%, prevalence of history of low birth weight was 19,6%, prevalence of history of respiratory infections was 76,1%, prevalence history of diarrhea was 39,1%. The numbers of subjects who had sufficient intakes of protein and zinc were 60,9% and 37%, respectively. There were correlations between history of low birth weight (p: 0,038), history of upper respiratory infections (p: 0,005), intake of protein (p: 0,003), intake of zinc (p: 0,005) and stunted in children aged 7-24 months. There was not correlation between diarrhea history (p: 0,851) and stunted in children aged 7-24 months.